On-the-land with Project Jewel: A Community-based Research Project in the Inuvialuit Settlement Region - Ollier, Mary (Université d'Ottawa / University of Ottawa, 2019)
In the Northwest Territories, there is a growing demand for knowledge about the effectiveness of land-based programs (GNWT Social Services Research Agenda, 2017). Project Jewel is a community-driven, land-based healing program in the Inuvialuit Settlement Region (ISR) that is run by the Inuvialuit Regional Corporation (IRC). My thesis, which is written in the two-publishable paper format, presents community-based research with Inuvialuit in the ISR. In paper one, we used postcolonial theory, a decolonization framework, and critical Inuit studies to approach an examination of how an evaluation of Project Jewel could promote cultural safety. The findings enabled us to create an evaluation framework that included centring the land, building relationships, working with words and pictures, and promoting benefits while minimizing harms through aftercare as elements identified by Project Jewel participants and staff that would enhance the likelihood of the evaluation being culturally safe. In paper two, we used the same methodology and theoretical approach to examine the elements of success and benefits of participation in Project Jewel. The findings identified that the elements of success for Project Jewel included Inuvialuit cultural practices, local programming, distraction and judgement free environment, confidentiality, and comfort and support. The benefits of participating in Project Jewel included (re)connection to land, culture, identity and heritage, strengthened systems of social support, and enhanced skills and self-esteem. Together, the two papers contribute to the further development of land-based programs for Inuvialuit in a way that is determined and led by Inuvialuit and their values. They demonstrate that land-based programs like Project Jewel can contribute to processes of decolonization and healing among Inuit that hold implications for improving/supporting positive health and wellbeing.